Antibacterial efficacy of endodontic irrigating solutions and their combinations in root canals contaminated with Enterococcus faecalis - Dornelles-Morgental, Renata [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; de Faria-Junior, Norberto Batista [UNESP]; Hungaro-Duarte, Marco Antonio; Kuga, Milton Carlos [UNESP]; Tanomaru-Filho, Mario [UNESP] (Mosby-elsevier, 2011)
Objective. The objective of this study was to evaluate the antibacterial efficacy of irrigating solutions and their combinations against Enterococcus faecalis.Study design. One hundred ten single-rooted human teeth were inoculated with E. faecalis and incubated for 21 days. Teeth were divided according to the irrigant: Group I (GI), 2.5% sodium hypochlorite solution (NaOCl); GII, 2.5% NaOCl + 10% citric acid; GIII, 2.5% NaOCl + apple cider vinegar; GIV, apple cider vinegar; GV, 2% chlorhexidine solution; GVI, 1% peracetic acid; GVII, saline solution. Microbiological samples were taken after root canal preparation and 7 days later. Data were submitted to ANOVA (5%).Results. All solutions promoted reduction of E. faecalis after instrumentation, but bacterial counts were higher in the final sample. GI, GV, and GVI had lower bacterial counts than the other groups.Conclusions. The irrigating solutions may present activity but do not eradicate E. faecalis in the root canal system. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2011; 112:396-400)